CW-CO2 Laser photoinitiated polymerization of Methyl Methacrylate - Hussain A. Jawad; Awatif S. Jassim; Youisf B. Yousif (College of Education for Pure Sciences, 2010)
Abstract Photoinitiated polymerization of methyl methacrylate has been observed using cw-CO2 laser radiation of (10.6 µm). Both of DSC and TGA thermal analysis techniques were used for identification of the thermal characteristics (Tg, Tc, and Tm) as well as the thermal stability of the laser photoinitiated PMMA and they compared with that corresponding to classical, conventionally initiated PMMA. In cw-CO2 laser radiation, each of powers (10, 15, and 20W) was used. Although a definite increase in Tg value and thermal stability were observed while power are (10W,15W and 20W), the polymerization pattern remained basically the same in all these cases. Multi-Photon absorption reaction phenomenon was attributed to elucidate the mechanism of interaction between the CO2 laser light and MMA monomer molecule.